A handbook of biblical Hebrew : Volume 1: periods, corpora, and reading traditions - Garr, W. Randall; Fassberg, Steven E., 1956- (Eisenbrauns, 2016)
"Biblical Hebrew is studied worldwide by university students, seminarians, and the educated public. It is also studied, almost universally, through a single prism--that of the Tiberian Masoretic tradition, which is the best attested and most widely available tradition of biblical Hebrew. Thanks in large part to its endorsement by Maimonides, it also became the most prestigious of vocalization tradition in the Middle Ages. For most, biblical Hebrew is synonymous with Tiberian biblical Hebrew. There are, however, other vocalization traditions. What is still lacking is a comprehensive and systematic overview of the different periods, sources, and traditions of biblical Hebrew. This handbook provides students and the public with easily accessible, reliable, and current information in English concerning the multi-faceted nature of biblical Hebrew. Noted scholars in each of the various fields contributed their expertise. The result is the present two-volume work. The first contains an in-depth introduction to each tradition; and the second presents sample accompanying texts that exemplify the descriptions of the parallel introductory chapters"--